Effects of Dry and Liquid Pellet Binder Inclusion and Conditioning Temperature on Pellet Mill Efficiency and Pellet Quality of a High-Fiber Ruminant Ration - Caitlin E. Evans; Marut Saensukjaroenphon; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
The objectives of this experiment were: 1) to determine the effects of sucrose and lactose-based liquid ingredient inclusion on the pelleting efficiency and quality of a high-fiber diet; and 2) to evaluate the role of mash conditioning temperature on the binding effectiveness of the tested liquid ingredients. Binders included DLS (dry calcium lignosulfonate), LCM (liquid cane molasses), LMB (commercial liquid molasses blend), and LLB (commercial liquid lactose blend). Treatments were arranged in a 5 × 3 factorial of pellet binder (control, DLS, LCM, LMB, and LLB) and conditioning temperature (165, 175, and 185°F). Data were analyzed using the GLIMMIX procedure of SAS with linear and quadratic contrasts for increasing conditioning temperature. Treatments were arranged in a completely randomized design and replicated 3 times. Diets were conditioned for approximately 40 s and pelleted with a 0.19 × 1.75 in. die at a rate of 3.0 ton/h. Pellet durability index (PDI) was determined using the standard and modified tumble box methods. There was no evidence of an interaction (P>0.209) between binder type and conditioning temperature when determining PDI according to either the standard or modified tumble box methods. Conditioning temperature alone did not affect PDI (P>0.119); however, differences were observed based on binder inclusion according to either method (P<0.046). Using the standard method of analysis, PDI was improved (P<0.046) by LCM and LLS addition compared to both the control and LCM diets, while LLB was intermediate. According to the modified method with greater agitative stress, PDI was improved (P<0.005) when using LCM and LLB compared to the control diet, with DLS and LCM being intermediate. Additionally, LCM inclusion reduced (P<0.001) pellet mill throughput and increased (P<0.001) energy consumption of the pellet mill motor compared to the control and other binders, with no observed differences (P<0.269) resulting from increased conditioning temperature. Under the constraints of this trial, cane molasses and commercial molasses and lactose blends were shown to be effective pellet binders, regardless of conditioning temperature when included in a high-fiber ration. However, challenges with molasses handling characteristics and increased friction at the die interface may reduce its practical application and encourage the use of the alternative commercial blends.
Keywords: pellet binder; conditioning temperature; lignosulfonate; molasses; lactose; feedlot; feed; beef; pellet quality; ruminant rations